2020
DOI: 10.1021/acs.est.9b05869
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Perfluoroalkyl Ether Carboxylic Acids with Hydrated Electrons: Structure–Reactivity Relationships and Environmental Implications

Abstract: This study explores structure–reactivity relationships for the degradation of emerging perfluoroalkyl ether carboxylic acid (PFECA) pollutants with ultraviolet-generated hydrated electrons (eaq –). The rate and extent of PFECA degradation depend on both the branching extent and the chain length of oxygen-segregated fluoroalkyl moieties. Kinetic measurements, theoretical calculations, and transformation product analyses provide a comprehensive understanding of the PFECA degradation mechanisms and pathways. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
151
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(162 citation statements)
references
References 45 publications
8
151
3
Order By: Relevance
“…While the molecular control of the redox‐copolymer allows for the selective separation of organic contaminants, the fate of the enriched pollutant waste after separation process must be addressed. [ 18 ] Here, we propose a unique approach to achieve tandem separation and degradation of the model compound PFOA within the same electrochemical unit, by leveraging an asymmetric electrochemical design that combines the P(TMA x ‐ co ‐TMPMA 1− x )‐functionalized CNT working electrode with a BDD counter electrode. While the redox‐copolymer acts as a selective adsorbent, the BDD counter‐electrode acts as a synergistic electrocatalyst during the regeneration step.…”
Section: Resultsmentioning
confidence: 99%
“…While the molecular control of the redox‐copolymer allows for the selective separation of organic contaminants, the fate of the enriched pollutant waste after separation process must be addressed. [ 18 ] Here, we propose a unique approach to achieve tandem separation and degradation of the model compound PFOA within the same electrochemical unit, by leveraging an asymmetric electrochemical design that combines the P(TMA x ‐ co ‐TMPMA 1− x )‐functionalized CNT working electrode with a BDD counter electrode. While the redox‐copolymer acts as a selective adsorbent, the BDD counter‐electrode acts as a synergistic electrocatalyst during the regeneration step.…”
Section: Resultsmentioning
confidence: 99%
“…This explains the long residence times to achieve mineralization, especially in complex solutions, because as the fluorinated alkyl chain shortens, the associated bond dissociation energy necessary to achieve defluorination increases while the potential for rapid scavenging reactions remains constant. The perfluoroalkyl ether compounds (e.g., “Gen X”) that have become more prevalent in recent years have higher bond dissociation energies adjacent to the ether linkages, making these molecules less likely to exchange fluorine for hydrogen in ARP‐mediated defluorination and form recalcitrant by‐products (Bentel et al ). By‐products that have been detected in the ARP treatment of perfluoroalkyl ethers are predominantly polyfluorinated ether compounds (Bentel et al ).…”
Section: Considerations For Available Pfas‐relevant Destruction Technmentioning
confidence: 99%
“…The perfluoroalkyl ether compounds (e.g., “Gen X”) that have become more prevalent in recent years have higher bond dissociation energies adjacent to the ether linkages, making these molecules less likely to exchange fluorine for hydrogen in ARP‐mediated defluorination and form recalcitrant by‐products (Bentel et al ). By‐products that have been detected in the ARP treatment of perfluoroalkyl ethers are predominantly polyfluorinated ether compounds (Bentel et al ).…”
Section: Considerations For Available Pfas‐relevant Destruction Technmentioning
confidence: 99%
“…In contrast to oxidative processes, reduction involves the direct transformation of electrons from a reducing agent with a lower reduction potential compared to the substrate. Advanced reduction processes (ARPs), reductive metals (e.g., zero-valent iron (ZVI)), hydride radicals (H·) and most notably hydrated electrons (E 0 = −2.9 V) have been used to achieve the effective cleavage of C−F bonds in PFASs [ 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. The investigation of PFAS reduction reactions have shown that they are sensitive towards the choice of reagents, their concentrations and reaction times as well as pH value of the solution [ 74 , 75 , 76 ], thus can show variable efficiencies.…”
Section: State-of-the-art Liquid Reactionsmentioning
confidence: 99%
“…This finding was assigned to an elevated OH − concentration in solution since the degradation of PFASs in the presence of pure NaOH was reported previously (see also Section 2.1 ). In a different report, various perfluoroalkyl ether carboxylic acids (PFECAs) were degraded at a pH of 9.5 [ 73 ]. All compounds were degraded but the defluorination rates were only between 30 and 98% after 48 h of treatment.…”
Section: State-of-the-art Liquid Reactionsmentioning
confidence: 99%